2018
DOI: 10.1111/nhs.12539
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties of fathers whose families evacuated voluntarily after the Fukushima nuclear disaster

Abstract: The Fukushima nuclear disaster in 2011 resulted in radiation exposure, and many evacuees felt anxious of its health risks. However, little is known about the difficulties faced by fathers whose families evacuated voluntarily. Therefore, the aim of the present case study was to clarify the difficulties and concerns of fathers whose families evacuated voluntarily after the Fukushima nuclear disaster. Eleven fathers in Fukushima were interviewed between 14 December 2014 and 25 February 2015. Four themes emerged: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The prevalence of mental disorders was high overall in Fukushima survivors [20]. Many residents were also subjected to home evacuation, displacement, relocation, work/school changes, and family separation [19,21]. In addition, they had raised concerns about the safety of food and water [22].…”
Section: The Main Category: "Establishing a System In Advance Of A Large-scale Disaster"mentioning
confidence: 99%
“…The prevalence of mental disorders was high overall in Fukushima survivors [20]. Many residents were also subjected to home evacuation, displacement, relocation, work/school changes, and family separation [19,21]. In addition, they had raised concerns about the safety of food and water [22].…”
Section: The Main Category: "Establishing a System In Advance Of A Large-scale Disaster"mentioning
confidence: 99%
“…The difficulties and concerns of the self-evacuees were clarified by the fathers of the families who had chosen to evacuate voluntarily due to the FDNPS accident. It was reported that the fathers experienced a decline in both their physical and mental health because of the self-evacuation in their families [15]. Further, the process of self-evacuation in mothers with small children was clarified in a previous study.…”
Section: Introductionmentioning
confidence: 97%
“…Evacuees may nd it challenging if they cannot con de in family members. In many disasters, families evacuate together and continue their post-disaster lives toward recovery (10,11); however, in Fukushima prefecture, especially among the younger generation with children, there have been many cases of family separation, with only grandparents and fathers remaining in Fukushima owing to work, school, and radiation concerns (12,13). Nevertheless, few studies have reported the importance of con ding in family members during disasters in the context of the association with mental health conditions.…”
Section: Introductionmentioning
confidence: 99%